Let $(f_n)$- real sequence such that $$ \lim_{n\rightarrow \infty} \frac{f_{n+1}f_n-f_{n-1}f_{n+2}}{f_{n+1}^2-f_nf_{n+2}}=a+b, $$ and $$ \lim_{n\rightarrow \infty} \frac{f_{n}^2-f_{n-1}f_{n+1}}{f_{n+1}^2-f_nf_{n+2}}=ab \quad (|a|<|b|). $$

Prove that:$$\lim_{n\rightarrow \infty} \frac{f_n}{f_{n+1}}=a $$

I think we must prove $\displaystyle\lim_{n\rightarrow \infty} \frac{f_n}{f_{n+1}} $ exists,and we prove this limit is $a$,But I can't prove this limit exists.

My idea: since $$\lim_{n\to\infty}\dfrac{\dfrac{f_{n}}{f_{n+1}}-\dfrac{f_{n-1}}{f_{n}}\dfrac{f_{n}}{f_{n+1}}\dfrac{f_{n+2}}{f_{n+1}}}{1-\dfrac{f_{n}}{f_{n+1}}\dfrac{f_{n+2}}{f_{n+1}}}=a+b$$ and $$\lim_{n\to\infty}\dfrac{\left(\dfrac{f_{n}}{f_{n+1}}\right)^2-\dfrac{f_{n-1}}{f_{n}}\dfrac{f_{n}}{f_{n+1}}}{1-\dfrac{f_{n}}{f_{n+1}}\dfrac{f_{n+2}}{f_{n+1}}}=ab$$ But I felt this deal is not useful,

Other idea: I want to take the Fibonacci sequence to solve this problem, But I can't,

Thank you


This is a supplement to several other answers about existence of the limit.

Let $P_n = \left|\begin{matrix}f_{n+1} & f_{n+2}\\ f_{n-1} & f_n\end{matrix}\right|$ and $Q_n = \left|\begin{matrix}f_{n} & f_{n+1} \\ f_{n-1} & f_n\end{matrix}\right|$, the given condition can be rewritten as

$$\lim_{n\to\infty} \frac{P_n}{Q_{n+1}} = a + b \quad\text{ and }\quad\lim_{n\to\infty} \frac{Q_n}{Q_{n+1}} = ab\tag{*1}$$

Notice $$f_n P_n - f_{n+1}Q_n = f_{n-1} Q_{n+1} \quad\iff\quad f_{n+1} = \frac{P_n}{Q_n} f_n - \frac{Q_{n+1}}{Q_n} f_{n-1} $$ The sequence satisfies a non-linear recurrence relations whose coefficients converge to some finite limit. The "limit" of the recurrence relation has the form

$$f_{n+1} = \left(\frac{1}{a} + \frac{1}{b}\right) f_{n} - \frac{1}{ab} f_{n-1}$$

with characteristic polynomial $\lambda^2 - \left(\frac{1}{a} + \frac{1}{b}\right)\lambda + \frac{1}{ab} = \left(\lambda - \frac{1}{a}\right)\left(\lambda - \frac{1}{b}\right)$.

By assumption, $|a| < |b|$. This means distinct roots of this characteristic polynomial has distinct modulus. By Poincare-Perron theorem$\color{blue}{^{[1]}}$, we have either

  • $f_n = 0$ for all sufficiently large $n$ or
  • $\lim\limits_{n\to\infty} \frac{f_{n+1}}{f_n}$ exists and equal to $\frac{1}{a}$ or $\frac{1}{b}$.

The assumption $(*1)$ is written in such a way that $Q_{n+1}$ is non-zero for sufficient large $n$. So we can ignore the possibility that $f_n$ vanishes for large $n$. This implies the limit $\lim\limits_{n\to\infty} \frac{f_{n}}{f_{n+1}}$ does exist and equal to either $a$ or $b$.


  • $\color{blue}{[1]}$ For more details of Poincare-Perron theorem and a proof of it, please consult Chapter 8 of Saber Elaydi's book An Introduction to Difference Equations.
  • $\begingroup$ This essentially solves the main problem. As I understand, it also follows from at least some formulation of Poincare-Perron that the limit $1/a$ is the "general limit" while the limit $1/b$ can only occur in "special cases". I've tried to construct such a special case, but failed, and suspect that you might be able to find such a series of $f_n$ which satisfies the recurrence, but that it will not be able to satisfy both of the required limits. $\endgroup$ Mar 1 '14 at 11:04
  • $\begingroup$ And Barry Cipra has already proved that $1/a$ is the limit, not $1/b$. My bad for missing out on that. Thus, the result should be fully proved by the combined effort. $\endgroup$ Mar 1 '14 at 12:20

Sort of useful: let $g_n = \frac{f_n}{f_{n+1}}$, then

$$\lim_{n\to\infty} {g_n \frac{g_{n+1} - g_{n-1}}{g_{n+1} - g_n}} = a+b$$


$$\lim_{n\to\infty} {g_n g_{n+1}\frac{g_{n} - g_{n-1}}{g_{n+1} - g_n}} = ab$$

Notice that $\frac{g_{n+1} - g_{n-1}}{g_{n+1} - g_n} = 1 + \frac{g_{n} - g_{n-1}}{g_{n+1} - g_n}$, and letting $h_n = \frac{g_{n} - g_{n-1}}{g_{n+1} - g_n}$, obtain

$$\lim_{n\to\infty} {g_n (1 + h_n)} = a+b$$ and $$\lim_{n\to\infty} {g_n g_{n+1} h_n} = ab$$

Obviously, for $G = \lim_{n\to\infty} {g_n}$ to exist, so must $ H = \lim_{n\to\infty} {h_n}$. The rest is simple yet laborous:

  • Assume that the limits exist; take them; obtain a quadratic equation for $G$, it will yield $a$ and $b$ as roots (hence candidates for actual limit value).
  • Let $\epsilon_n = g_n - r$, where $r$ is the root of the quadratic equation from the previous step, and demonstrate that for lesser root $\epsilon$ diminishes (BTW that completes the proof of existence), while for the larger one it grows.

Note: I've rewritten things to incorporate a considerable simplification pointed out by Einar Rødland.

Here's part of a proof. Let's assume that $\lim_{n\to\infty}f_n/f_{n+1}$ exists, and show that it must equal $a$.

Since $|a|\lt|b|$, we have $b\not=0$, so we can write $f_n/f_{n+1}=bg_n$. (Note: This assumes $f_{n+1}\not=0$, which is justified since we're assuming the limit exists.) We now want to show that $\lim_{n\to\infty}g_n=a/b$. Let's write $r=a/b$. We know that $|r|\lt1$.

In terms of the $g$'s, we have the two limits

$$\lim_{n\to\infty}\left(g_n{g_{n+1}-g_{n-1}\over g_{n+1}-g_n}\right)=1+r$$


$$\lim_{n\to\infty}\left(g_ng_{n+1}{g_n-g_{n-1}\over g_{n+1}-g_n}\right)=r$$

Note that we must have $f_{n+1}^2-f_nf_{n+1}\not=0$ for all large $n$, which means that $g_{n+1}-g_n\not=0$ for all large $n$ as well.

The first limit can be rewritten as

$$\lim_{n\to\infty}\left(g_n+{1\over g_{n+1}}\left(g_ng_{n+1}{g_n-g_{n-1}\over g_{n+1}-g_n}\right)\right)=1+r$$

If we now assume that $\lim_{n\to\infty}g_n=G$ (i.e., the limit exists), then we have

$$G+{1\over G}r=1+r$$

which implies $G=1$ or $G=r$. We need to show that $G=1$ leads to a contradiction.

Suppose that $G=\lim_{n\to\infty}g_n=1$. Then

$$\lim_{n\to\infty}\left(g_ng_{n+1}{g_n-g_{n-1}\over g_{n+1}-g_n}\right)=\lim_{n\to\infty}\left({g_n-g_{n-1}\over g_{n+1}-g_n}\right)$$

from which we have

$$\lim_{n\to\infty}\left|g_{n+1}-g_n\over{g_n-g_{n-1}}\right|={1\over |r|}\gt1$$

This implies there is an $N$ such that $g_{N+n}-g_{N+n-1}\not=0$ and

$$\left|g_{N+n+1}-g_{N+n}\over{g_{N+n}-g_{N+n-1}}\right|\gt 1$$

for all $n\ge0$, and this implies

$$\left|g_{N+n}-g_{N+n-1}\over{g_{N}-g_{N-1}}\right|= \left|g_{N+n}-g_{N+n-1}\over{g_{N+n-1}-g_{N+n-2}}\right| \left|g_{N+n-1}-g_{N+n-2}\over{g_{N+n-2}-g_{N+n-3}}\right|\cdots \left|g_{N+1}-g_{N}\over{g_{N}-g_{N-1}}\right|\gt 1$$

for all $n$. But $\lim_{n\to\infty}(g_{N+n}-g_{N+n-1})=0$, and there's our contradiction.

Finally, the answer by achille hui, citing the Poincare-Perron theorem, shows that the limit does exist, so together this settles the OP's question.

  • $\begingroup$ +1 BTW, the limit does exist by Poincare-Perron theorem. $\endgroup$ Feb 27 '14 at 23:56
  • $\begingroup$ It seems to me the formulation could be simplified a bit. Assuming $g_n\rightarrow G$, you get that $|g_n-g_{n-1}|/|g_{n+1}-g_n|\rightarrow |r|/G^2$ (your second limit), and if this limit is less than 1, $|g_{n+1}-g_n|$ will increase for large $n$ and $g_n$ cannot converge. $\endgroup$ Mar 1 '14 at 12:30
  • $\begingroup$ @EinarRødland, thank you! I've rewritten the proof to simplify it. I don't know why I thought it had to be so complicated. $\endgroup$ Mar 1 '14 at 14:59

I'm going to post a failed approach, just so you can see what I tried. This is here only to show an approach and (maybe) generate new ideas.

Let $$x:=a+b\;\;\text{ and }\;\; y:=ab.$$ Assume for now $0<a<b$. Then $$\frac{x-\sqrt{x^2-4y}}{2} =\frac{a+b-\sqrt{(a+b)^2-4ab}}{2} =\frac{a+b-\sqrt{(a-b)^2}}{2} =\frac{a+b-\vert a-b\vert}{2} =\frac{a+b-b+a}{2} =a.$$ Now we replace $a+b$ with $\lim_{n\rightarrow \infty} \frac{f_{n+1}f_n-f_{n-1}f_{n+2}}{f_{n+1}^2-f_nf_{n+2}}$ and $ab$ with $\lim_{n\rightarrow \infty} \frac{f_{n}^2-f_{n-1}f_{n+1}}{f_{n+1}^2-f_nf_{n+2}}$, and due to continuity move the limit outside: $$\frac{a+b-\sqrt{(a+b)^2-4ab}}{2} =\lim_{n\to\infty} \frac{\left(\frac{f_{n+1}f_n-f_{n-1}f_{n+2}}{f_{n+1}^2-f_nf_{n+2}}\right)-\sqrt{\left(\frac{f_{n+1}f_n-f_{n-1}f_{n+2}}{f_{n+1}^2-f_nf_{n+2}}\right)^2 -4\left(\frac{f_{n}^2-f_{n-1}f_{n+1}}{f_{n+1}^2-f_nf_{n+2}}\right)}}{2} =\lim_{n\to\infty} \frac{\left({f_{n+1}f_n-f_{n-1}f_{n+2}}\right) -\sqrt{\left({f_{n+1}f_n-f_{n-1}f_{n+2}}\right)^2 -4\left({f_{n}^2-f_{n-1}f_{n+1}}\right)\left({f_{n+1}^2-f_nf_{n+2}}\right)}}{2\left({f_{n+1}^2-f_nf_{n+2}}\right)} =\lim_{n\to\infty} \frac{f_{n+1}f_n-f_{n-1}f_{n+2} -\sqrt{ f_{n+1}^2f_n^2 -2f_{n+1}f_n f_{n-1}f_{n+2} +f_{n-1}^2f_{n+2}^2 -4f_n^2f_{n+1}^2+4f_{n}^2f_nf_{n+2}+4f_{n-1}f_{n+1}f_{n+1}^2-4f_{n-1}f_{n+1}f_nf_{n+2}} }{2\left({f_{n+1}^2-f_nf_{n+2}}\right)} $$ At this point there are no useful simplifications to be done inside the radical. It does not seem to agree with the $x$ and $y$ case.


I thought this was a counter-example, until reminded that $|a|<|b|$ was required.

For any two numbers $u,v$, let $f_{2k}=u$ and $f_{2k+1}=v$. The expressions in the two limits will then both be constant, with $a+b=0$ and $ab=-1$: real number solutions are $(a,b)=(1,-1)$ and $(-1,1)$. Now, $f_n/f_{n+1}$ will alternate between $u/v$ and $v/u$, and thus not converge (unless $u=\pm v$). However, $|a|=|b|$, so it's not a proper counter-example.

Another attempt I made was to have $f$ loop over values $0,1,-1$, but that would make $a+b=-1$ and $ab=1$ which has no real solutions.

  • 2
    $\begingroup$ This is no counter example, because $|a|<|b|$ and thus $a = -b $ is not possible $\endgroup$
    – Stefan
    Feb 27 '14 at 17:12
  • $\begingroup$ @Stefan: True! I overlooked that requirement. $\endgroup$ Feb 27 '14 at 18:22

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.